2003
DOI: 10.1002/uog.885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the measurement of the fetal fat layer, interventricular septum and abdominal circumference percentile in the prediction of macrosomia in pregnancies affected by gestational diabetes

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 28 publications
(29 reference statements)
0
30
1
2
Order By: Relevance
“…In another study by Bethune et al, [5], showed that fetal fat layer or subcutaneous tissue thickness >5mm was more useful than abdominal circumference as a predictor of macrosomia in 90 pregnancies affected by gestational diabetes, but only took one measurment between 28 and 34 weeks. Parretti et al, [6] investigated AAW thickness specifically in the fetuses of those with impaired glucose tolerance in pregnancy, and showed that AAW thickness increased significantly from 26 weeks compared to normal levels.…”
Section: Introductionmentioning
confidence: 98%
“…In another study by Bethune et al, [5], showed that fetal fat layer or subcutaneous tissue thickness >5mm was more useful than abdominal circumference as a predictor of macrosomia in 90 pregnancies affected by gestational diabetes, but only took one measurment between 28 and 34 weeks. Parretti et al, [6] investigated AAW thickness specifically in the fetuses of those with impaired glucose tolerance in pregnancy, and showed that AAW thickness increased significantly from 26 weeks compared to normal levels.…”
Section: Introductionmentioning
confidence: 98%
“…The severity of symptoms of respiratory failure and congestive heart failure correlate with the severity of hypertrophic cardiomyopathy 22,23 . The measurement of the interventricular septum thickness has been traditionally performed by fetal echocardiography using the M mode 10,11,24 , however, this measure has inaccuracies, since the interventricular septum is not a uniform structure.…”
Section: Gestational Age (Weeks) Septum Thickness IV (Mm)mentioning
confidence: 99%
“…This would be a way to directly analyze septal defects, which are the most common congenital heart defects, accounting for about 30% of heart diseases, especially membrane defects 1 , also analyzing indirectly other cardiac malformations (such as valvular stenoses with consequent ventricular hypertrophy, among others). Moreover, the valve area measurement will allow the early detection of septal hypertrophy in fetuses of diabetic pregnant women, by tracking fetuses with greater likelihood of developing macrosomia and cardiomyopathy 10,11 . This study aims to determine reference values for the interventricular septum area of normal fetuses between the 18 th and the 33 rd pregnancy week through the US3D by using the method STIC.…”
mentioning
confidence: 99%
“…Ova doktorska disertacija potvrdila je značajno veću učestalost svih ultrazvučnih markera GDM-a u trudnica kod kojih je ustanovljeno prisustvo ovog patološkog entiteta (p<0.0001), a što je u saglasnosti sa velikim brojem studija koje su se bavile ovom problematikom (Breitweser et al, 1980;Hornberger 2006;Larciprete et al, 2003;Badalian et al, 1996;Zamlynski et al, 2005;Vink et al, 2006;Maulik et al, 2002;Thompson et al, 2002;Bethune et Bell, 2003;Guariglia et al, 2006;Awadh et al, 2006;Merz et Weber, 2005). Među obolelim trudnicama, od svih posmatranih markera najčešće je prisutna placentalna nezrelost, koja se javljala u 88.6% obolelih, a posle nje sledi povećana placentalna debljina sa 79.5% i zadebljani IVS i intenzivirani disajni pokreti koji su bili zastupljeni u 77.3% slučajeva.…”
Section: Ultrazvučni Markeri šEćerne Bolesti Trudnicaunclassified
“…Takođe, univarijantna regresiona analiza pokazala je da je svaki od evaluiranih markera, odnosno konstituenata predloženog ultrazvučnog skora prediktor GDM-a, što je u saglasnosti sa velikim brojem studija (Weber et al, 1991;Gandhi et al, 1995;Breitweser et al, 1980;Hornberger 2006;Larciprete et al, 2003;Badalian et al, 1996;Zamlynski et al, 2005;Vink et al, 2006;Maulik et al, 2002;Thompson et al, 2002;Bethune et Bell, 2003;Guariglia et al, 2006;Awadh et al, 2006;Merz et Weber, 2005). Upravo ovakvi rezultati opravdavaju nazive kao što su "ultrazvučni markeri gestacionog dijabetesa" i "ultrazvučni markeri glikemijske kontrole", a koji se koriste u opisivanju konstituenata predloženog ultrasonografskog skora u otkrivanju šećerne bolesti trudnica.…”
Section: Ultrazvučni Markeri šEćerne Bolesti Trudnicaunclassified